Biochemical analysis reveals the systematic response of motion sickness mice to ginger (Zingiber officinale) extract's amelioration effect. (23rd May 2022) - Zhong, Wanlin; Zhu, Jiaqing; Yi, Juanjuan; Zhao, Changcheng; Shi, Yanling; Kang, Qiaozhen; Huang, Jinyong; Hao, Limin; Lu, Jike
Abstract: Ethnopharmacological relevance: As a common medicinal and edible plant, Zingiber officinale Roscoe (ginger) is often used for the prevention of motion sickness. However, the mechanism of its anti-motion sickness remains to be elucidated. Aim of the study: To explore novel treatment for motion sickness with less side effects, anti-motion sickness effect of ginger (Zingiber officinale) extract (GE) and the possible molecular mechanisms were investigated. Materials and methods: The anti-motion sickness effect of ginger was evaluated through mice animal experimental models. Components of ginger that might contribute to the anti-motion sickness effect were analyzed by LC-MS/MS. Subsequently, biochemical analysis integrated with serum metabolomic profiling were performed to reveal the systematic response of motion sickness mice to ginger extract's amelioration effect. Results: Exhaustive swimming time of mice in the GE group reached 8.9 min, which was 52.2% longer than that in the model group. Motion sickness index scores and time taken traversing balance beam of mice in the GE group were decreased by 53.2% and 38.5%, respectively. LC-MS/MS analysis suggested that various active ingredients in GE, such as gingerol, ginger oil and terpenoids, might contribute to its appealing anti-motion sickness activity. Biochemical analysis revealed that GE can relieve motion sickness through reducing histamine and acetylcholine release in vestibular system, regulating fatty acid oxidation, sugar metabolism and bile acid metabolism in mice. Conclusion: Gavage of mice with GE can effectively relieve the symptoms of autonomic nervous system dysfunction, improve the balance and coordination ability and ameliorate the ability to complete complex work after rotation stimulation. GE has attractive potential for development and utilization as novel anti-motion sickness food or drugs. Graphical abstract: Image 1 Highlights: Motion sickness index of ginger extract (GE) group mice was decreased by 53.2%. Swimming time of GE group mice reached 8.9 min, 52.2% longer than model mice. Gingerol, ginger oil and terpenoids in GE might contribute to anti-motion sickness. GE reduced acetylcholine and histamine content in motion sickness mice. GE regulated sugar, fatty acid and bile acid metabolism to relief motion sickness.